Medical apartheid in Palestine - Yazid Barhoush; Joseph J. Amon (Taylor & Francis Group, 2023)
The International Convention on the Suppression and Punishment of the Crime of Apartheid (1974) and Article 7 of the Rome Statute of the International Criminal Court (1998) recognise apartheid as a crime against humanity, characterised by a practice of systematic oppression and violations of human rights with the intent of one racial group to maintain domination over another. The term 'medical apartheid', although without a formal definition in international human rights law, has been used similarly to refer to situations of pervasive segregation and discrimination in health care, based upon race, and characterised by stark inequality in health care accessibility, availability, acceptability, and quality. This paper, using a combination of literature review; data on attacks on Palestinian health facilities, workers, and transport; and information from Palestinian and Israeli government authorities on referrals to specialised health care services, examines the ways in which Israeli policies and practices can be understood to constitute a form of 'medical apartheid' that deprives Arab residents of the Palestinian territories the full realisation of their right to health.